THE INKA ARMY, an approximation - Hurtado Frisancho, Ivan (2023)
This article describes the inka army, through the analysis of weapons, tactical organization, and command; thus, the objective of finding interrelations between inka warfare, social organization, and power. So, this is how through an explanation about the use and importance of the armament, we go to determine the order of the tactical formations based on the society configuration in ayllus and their space ideal distribution, so we can finally interpret the leadership of this organization, so that way establish a tight relation with the power structure, not only about the warfare but also about the religion and the administration. This allow us to understand social tension and conflict for the power, that were produced into the inka society at the beginning and at the end of a conquest campaign, and approximated to the use of the inka’s llaqtas as military centers related to the panakas or linages and their importance inside the power and succession conflicts. This analysis allows us to rethink some premises of the actual historiography about a supposed decimal and dual organization of the army, nevertheless that both the military and social structure conditioned a unique command that inside the Andean world possibly constituted a unique and decisive advantage and characteristic of the inka army.